Dissipativity-based filter design for Markov jump systems with packet loss compensation. (November 2021) - Xue, Min; Yan, Huaicheng; Zhang, Hao; Shen, Hao; Shi, Peng
Abstract: This paper is concerned with the dissipativity-based filtering problem for a class of discrete-time Markov jump systems with mode-dependent time-varying delays and random packet losses. The phenomenon of packet losses occurs between the plant and the filter, which is characterized by introducing a random variable. Based on the single exponential smoothing method, the prediction of the missing measurement is used as the packet loss compensation when a packet is lost. Then, a partially mode-dependent filter is established in view of the fact that the mode signals of the original system may not be completely accessible to the filter. By employing a mode-dependent Lyapunov-Krasovskii functional, some novel sufficient conditions are obtained and the filter parameters are derived to ensure that the filtering error system is stochastically stable with a strictly ( U, V, W )- γ -dissipative performance. Finally, a numerical example is utilized to demonstrate the effectiveness of the proposed approach.